Role and importance of elastography in the diagnosis of differentiated thyroid carcinomas regarding the clinical, echosonographic, biohumoral and cytological examination and correlation of these results with definitive histopathological findings – A retro - Kiković, Saša; Marinković, Dejan M.; Ristić, Petar; Karajović, Jelena; Kuzmić-Janković, Snežana; Djuran, Zorana; Čizmić, Milica; Kovačević, Božidar; Nenezić, Nemanja; Hajduković, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Thyroid nodules represent a common problem in medicine. Ultrasound examination of the thyroid glands is a common method for the initial diagnosis of thyroid neoplasia enabling the selection of nodules that should undergo fine needle aspiration biopsy (FNAB). It is a noninvasive method that has a great potential in discovering suspicious lesions, enabling timely actions for further diagnostics and potential treatment. However, it is still not clear enough how the quantitative data collected from Ultrasound elastography correlate with those obtained by other diagnostic tools used for detecting thyroid nodules. The aim of this study was to estimate the importance of ultrasound elastography in diagnostics of differentiated thyroid carcinomas but also to estimate the importance of other diagnostic procedures as well. Methods. The research was performed on patients initially referred to the Clinic of Endocrinology in Military Medical Academy, Belgrade to evaluate the status of thyroid nodules. The data from ultrasound elastography was then correlated with those from other diagnostic procedures including clinical examination, echosonography, cytological and histopathological analyses. Results. Statistically significant difference between the group of patients with follicular adenoma and the group of patients with differentiated thyroid carcinoma was detected for consistency, nodules immovability, thyroglobulin (Tg) levels, presence of calcifications in the nodules and the elastographic score. Fixed nodules and those with firmer consistency were significantly more common in the group of patients with malignant lesions, in which Tg levels were higher. The elastography score 3–4 showed a high predictive value for the detection of thyroid carcinoma, unlike the elasticity score. Conclusion. Ultrasound elastography represents a new non-invasive method that has a very significant, high predictive value for the detection of thyroid carcinoma, especially in correlation with other diagnostic procedures.
Keywords: thyroid diseases; ultrasonography; biopsy, fine-needle; diagnosis; differential.